Experiences experienced by patients diagnosed with panic disorder (Research, Society and Development, 2022)
Introduction: panic disorder is characterized by recurrent panic attacks, which cause, among other symptoms, shorty, shorty of hyperventilation, high blood pressure, asphyxia, nausea, abdominal discomfort, dizziness and chest pain. Objective: to know the experiences of patients diagnosed with Panic Disorder about the disease. Methods: the study was conducted through the reports collected with the patients themselves in a qualitative approach, which offers a privileged perspective for understanding this personal and global aspect of the experience of the disorder. A semi-structured script was used, which records socioeconomic data, leisure information, and questions related to the disease. Results: five patients participated in the study, 5 female, the analysis of the reports revealed the growing need for information on this issue that is still very new in society. Conclusion: living with panic disorder is a significant challenge for the individual's life, which requires social, family and health services support.